Instrumental neutron activation analysis to determine inorganic elements in paddy soil and rice and evaluate bioconcentration factors in rice - Seeprasert, Prapamon; Anurakpongsatorn, Patana; Laoharojanaphand, Sirinart; Busamongkol, Arporn (Agriculture and Natural Resources, 2017)
Increased anthropogenic activity, especially in thriving industries and mining activity, has led to the accumulation of inorganic elements in the soil. This study applied neutron activation analysis for the determination of inorganic element concentrations in paddy soils and quantified the nutrient value of paddy rice cultivated on various agricultural sites throughout Thailand. The determination accuracy of the elements-U, As, Sb, W, Mn, K, La, Cr, Hf, Cs, Sc, Fe, Co, Cd and Zn was assessed using National Institute of Standards and Technology standard reference materials; the results were satisfactory, showing low relative error. High analytical precision was also observed. Cadmium was selected to check the linearity of the calibration curve against a Cd standard. For a calibration curve in the range 1-9 µg, a correlation coefficient of 0.997 was found. Trace amounts of U, As, Sb, W, Mn, K, La, Cr, Hf, Cs, Sc, Fe, Co, Zn and Cd were also found in the soil samples. However, the Co, Cd, and Zn concentrations were especially high in agricultural sites in Tak province. The elemental concentrations in rice followed the order K > Zn > Mn. The data obtained are of potential benefit for the development of trace element supplementation in food.